Steer gains on burned and nonburned bluestem pasture, 1978 to 1982 - Smith, E.F.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station, 2010)
From 1978 to 1982, steers on a late spring burned pasture averaged 40 lbs more gain each summer than steers on a non-burned pasture.
Keywords: Beef; Gain; Steer; Bluestem